THE INFLUENCE OF SOCIOECONOMIC STATUS ON THE LEVEL OF EARLY-SCHOOL-AGED CHILDREN’S MOTOR ABILITIES – BLURRING OF DIFFERENCES IN THE ECONOMICALLY UNDERDEVELOPED AREAS - Podstawski, Robert; Borysławski, Krzysztof; Kajmowicz, Bartosz (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Aim: The aim of the study was to determine differences in the level of motor abilities of 7-9-year-old girls and boys in relation to the socioeconomic status of their families . Material and Methods: The research was conducted in 12 primary schools in two regions of Poland namely of Warmia & Mazury and Pomorskie voivodeship, on the total of 1205 pupils (584 boys and 621 girls) aged 7-9. Selected economic factors such as the type of school (public or private), monthly income per household member, and the number of children in a given family were accepted as the independent variables. The factors behind social status included the place of residence and parents’ educational background. In order to determine the level of motor abilities, 13 motor tests were applied. Results: The research revealed that motor tests such as 1 and 3 min. Burpee test and medicine ball throws (forward and backward) appeared to show the biggest differences in the level of motor abilities of the children whose social and economic status varied. The results of these tests as well as those of the shuttle run were significantly higher for the girls from the families of high social status than for the boys of low social status. Social status to a greater extent than economic one differentiated the tested motor abilities, especially in the case of the girls from families marked by high social status, who scored better than boys. The exception is the skipping with clapping of hands – 8 s trial, which differentiated only the tested categories of economic status, especially when referred to the girls. Conclusions: Owing to the small number of significant differences between high and low social and economic status in both sex groups in the motor tests applied, it can be assumed that in the less developed, agriculture and tourism-oriented areas there has occurred blurring of the differences in the level of children’s motor abilities depending on their social and economic status.